Treated Follicular Lymphoma, Recurrent Invasive Pneumococcal Disease, Nonresponsiveness to Vaccination, and a Unique Pneumococcus - Murphy, Clare; Inverarity, Donald; McGoldrick, Claire; Mitchell, Lindsay; Paterson, Pamela; Thom, Louise; Edwards, Giles (Case Reports in Hematology, 2012)
A nonneutropenic patient with treated low-grade non-Hodgkin’s (Follicular) lymphoma and secondary hypogammaglobulinemia recovered from pneumococcal pneumonia and septicemia (serotype 7F; ST191) subsequent to influenza A H1N1 (2009). Both infections were potentially vaccine preventable. The patient then developed pneumococcal meningitis due to a serotype 35F pneumococcus with a unique Multilocus Sequence Type (ST7004) which was not vaccine preventable. Patient management was influenced by host predisposition to pneumococcal infection, antibiotic intolerance, and poor response to polysaccharide pneumococcal vaccine. Indirect immunofluorescence with anti-human immunoglobulin confirmed a poor or intermediate response to Pneumovax II. Prophylactic erythromycin was initiated, and immunoglobulin transfusions were also commenced as a preventive strategy. ST7004 is a single locus variant of ST1635 which has been associated with the serotype 35F capsule in England. The spi gene in ST7004, which differentiates it from ST1635, is the same as the spi gene present in ST191 which could have arisen from the first disease episode suggesting that horizontal gene transfer may have occurred between different populations of pneumococci present within the patient in an attempt to evade vaccination selection pressure.